Francisco Arcellana a life of fiction - Arcellana, Juaniyo; Yuson, Alfred; De la Cruz, Libertine Santos (Kuwadro., 2002)
Francisco Arcellana, writer, poet, essayist, critic, journalist and teacher, is one of the most important progenitors of modern Filipino short story in English. He edited and published Expression, a quarterly of experimental in writing in 1934 which spawned the Veronicans, a radical group of 13 prewar writers who rebelled against traditional forms and themes in Philippine literature. In his short stories, Arcellana explores the depths of human need and emotion in well-crafted prose.